(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Ergonomic Layout is one of the major influences on workers’ productivity; it can be significantly impacted by the layout of their workspaces and the equipment they use at work. Additionally, the layout and design of the workspace are essential for fostering inspiration, which has a positive impact on their job. The employees mustn't experience tiredness and discomfort since it can increase employee involvement. Employees must feel calm and relaxed to improve workplace productivity. Researchers were interested in knowing the impact of the Ergonomic Layout on Workers' Productivity. The leading findings are that most respondents are female from 25-30 years old, and most of them are Master’s Degree Holder. The main problem that researchers encountered is that employee should never compromise their health and bodily safety to complete a job. The employees must concentrate in a peaceful and quiet environment and rank in Strongly Agree as recommended offices should have comfortable chairs to support the spine of their employees and provide good lighting to reduce strain and avoid craning the neck. They must consider ergonomic efficiency posture, morale reinforces health, and provide guidance on their safe work procedures. Lastly, good relations with employees result from satisfaction. Based on the findings, researchers gathered to come up to the conclusion that the success of the organization is very much dependent on how its employees perform at the workplace and the respondents strongly agreed. Though the researchers desire to recommend to the department head that they should provide good lighting and high-quality equipment, should provide a monthly check-up for their safety and health, and have a wide space to move employees properly and not be crowded.